1987
DOI: 10.1177/000348948709600411
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer in Patients 70 Years of Age or Older

Abstract: This report presents our experience with 50 thyroid cancer patients 70 years of age or older, out of 606 patients of all ages. Comparing this series to those describing thyroid cancer patients of all ages, we found that thyroid carcinoma in the 70+ age group presents at a more advanced clinical stage, behaves more aggressively, and has a higher death rate. These findings are attributed mainly to the higher incidence of undifferentiated carcinoma and the more aggressive course of the differentiated types of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
2
9
1
1
Order By: Relevance
“…On analysing the histologic subtypes, we find that greater age coincides with a significant increase in undifferentiated forms in the group of patients over 70 years of age compared with patients aged between 51 and 70 years, and the latter compared with patients aged less than 50. This confirms the findings of a number of workers [23][24][25]; Har El [26] indicates a 30% incidence of anaplastic carcinomas of the thyroid in patients over the age of 70: this percentage is practically identical to the figure found by us (27.3%). Several authors [27,28] have shown that well-differentiated carcinomas that nevertheless display a more aggressive histotype, such a sclerosing and tall-cell papillary variants, have a higher incidence and an unfavourable evolution in patients aged over 50 years of age; these findings as were not confirmed by our study as Sautter Bihl findings [22].…”
Section: Discussionsupporting
confidence: 91%
“…On analysing the histologic subtypes, we find that greater age coincides with a significant increase in undifferentiated forms in the group of patients over 70 years of age compared with patients aged between 51 and 70 years, and the latter compared with patients aged less than 50. This confirms the findings of a number of workers [23][24][25]; Har El [26] indicates a 30% incidence of anaplastic carcinomas of the thyroid in patients over the age of 70: this percentage is practically identical to the figure found by us (27.3%). Several authors [27,28] have shown that well-differentiated carcinomas that nevertheless display a more aggressive histotype, such a sclerosing and tall-cell papillary variants, have a higher incidence and an unfavourable evolution in patients aged over 50 years of age; these findings as were not confirmed by our study as Sautter Bihl findings [22].…”
Section: Discussionsupporting
confidence: 91%
“…Har-El et al [27] observe that 30% of anaplastic thyroid carcinomas present in patients aged over 70 years. Furthermore, the prognosis for differentiated thyroid carcinoma is worse in geriatric patients [20,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies show that the increase in mortality with old age depends more on biological age than chronological age [9], and on the number of associated comorbidities [7,12,[24][25][26][27]. It must be remembered that geriatric patients who are undergoing thyroid surgery present with high co-morbidity, whether it be neurological, pneumological, or cardiac, etc., with rates ranging from 50% to 95% [6], and several with various associated comorbidities [6], and that this variation in percentages depends mainly on the variation in old age (65-80 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So fanden Har‐El et al. bei Patienten über 70 Jahren einen Anteil von 30 % anaplastischer Karzinome gegenüber 7,4 % in allen Altersgruppen (7). Auch in unserem Krankengut war der Anteil anaplastischer Karzinome mit 33 % der von den Thyreozyten ausgehenden Karzinome besonders hoch.…”
Section: Diskussionunclassified